Inequality of opportunity during the great recession in Uganda - Paolo Brunori; Flaviana Palmisanoy; Vito Peraginez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The paper proposes an analysis of the recent distributional dynamics in Uganda. This analysis is performed by endorsing an opportunity egalitarian perspective, in order to evaluate the outcome dynamics of specific groups of the population and infer the role of growth in the evolution of inequality of opportunity over time. We show that despite a reduction in the real value of the household consumption and a surge in outcome inequality between 2009/10 and 2010/11, the consumption dynamic appears to alleviate inequality of opportunity in Uganda.
Keywords: D63; F43; F61; F63; 330; inequality; inequality of opportunity; Uganda; great recession